2010 6th IEEE International Conference on Wireless, Mobile, and Ubiquitous Technologies in Education 2010
DOI: 10.1109/wmute.2010.52
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration with Mobile Media: Shifting from 'Participation' to 'Co-creation'

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…In the new optional part of the exercises, a number of open problems may be framed by the teachers accordantly to the topics in the syllabus. Such approach is agreed with the decades of research, confirming that collaborative learning presents powerful dynamics for knowledge building and supports education at individual, group, and institutional levels [14].…”
Section: Mechatronics Electronicssupporting
confidence: 62%
“…In the new optional part of the exercises, a number of open problems may be framed by the teachers accordantly to the topics in the syllabus. Such approach is agreed with the decades of research, confirming that collaborative learning presents powerful dynamics for knowledge building and supports education at individual, group, and institutional levels [14].…”
Section: Mechatronics Electronicssupporting
confidence: 62%
“…Firstly, as she performed the task on her own and during a quiet period, she felt unsupported without any peers with whom to relate or take a lead from. As noted by other researchers [7,14] this feedback highlights the value of peer support when engaging with mobile learning technologies.…”
Section: Individual Experiencessupporting
confidence: 62%
“…Similarly, Hussain [39] noticed that sharing learning experiences between students via OSNs is linked to developing the virtual community across the world. Lewis et al [52] (p. 112) called them "collaborative knowledge building communities". In addition, another study that took place in USM (Universiti Sains Malaysia), revealed that 300 students consider Facebook as a valuable and important tool that could support and enhance their language skills in English [20].…”
Section: Enhancing Educational Processesmentioning
confidence: 99%